Cytoplasmic poly (A) binding protein (PABPC2) critically regulates epidermal maintenance and turnover in planarian Schmidtea mediterranea - Bansal, Dhiru; Kulkarni, Jahnavi; Nadahalli, Kavana; Lakshmanan, Vairavan; Krishna, Srikar; Sasidharan, Vidyanand; Geo, Jini; Dilipkumar, Shilpa; Pasricha, Renu; Gulyani, Akash; Raghavan, Srikala; Palakodeti, Dasaradhi (Development (Cambridge), 2017)
Identifying key cellular events that facilitate stem cell function and tissue organization is critical for understanding the process of regeneration. Planarians are powerful model system to study regeneration and stem cell (neoblast) function. Here, using planaria, we show that the initial events of regeneration, such as epithelialization and epidermal organization are critically regulated by a novel cytoplasmic Poly A binding protein, SMED-PABPC2. Knockdown (KD) of Smed-pabpc2 leads to defects in epidermal lineage specification, disorganization of epidermis and ECM, and deregulated wound healing resulting in the selective failure of neoblast proliferation near the wound region. Polysome profiling suggested epidermal lineage transcripts, including zfp-1, to be translationally regulated by SMED-PABPC2. Together, our results uncover a novel role of SMED-PABPC2 in the maintenance of epidermal and ECM integrity, critical for wound healing, and subsequent processes for regeneration.